3-Weeks of Exercise Training Increases Ischemic-Tolerance in Hearts From High-Fat Diet Fed Mice - Boardman, Neoma T.; Rossvoll, Line; Lund, Jim; Hafstad, Anne D.; Aasum, Ellen (Frontiers in Physiology, 2019)
Physical activity is an efficient strategy to delay development of obesity and insulin resistance, and thus the progression of obesity/diabetes-related cardiomyopathy. In support of this, experimental studies using animal models of obesity show that chronic exercise prevents the development of cardiac dysfunction. Whether exercise also improves the tolerance to ischemia-reperfusion in these models is less clear, and may depend on the type of exercise procedure as well as time of initiation. We have previously shown a reduction in ischemic-injury in diet-induced obese mice, when the exercise was started prior to the development of cardiac dysfunction in this model. In the present study, we aimed to explore the exercise-mediated effect using a protocol that resembled a therapeutic, rather than preventive approach. Male C57BL/6J mice were fed a high-fat diet (HFD) for 20-22 weeks, where they were subjected to high-intensity interval training (HIT) during the last 3 weeks of the feeding period. Sedentary HFD fed and chow fed mice served as controls. Left-ventricular (LV) post-ischemic functional recovery and infarct size were measured in isolated perfused hearts. We also assessed the effect of 3-wk HIT on mitochondrial function and myocardial oxygen consumption (MVO2). Sedentary HFD fed mice developed marked obesity and insulin resistance, and demonstrated reduced post-ischemic cardiac functional recovery and increased infarct size. Three weeks of HIT did not induce cardiac hypertrophy and only had a mild effect on obesity and insulin resistance. Despite this, HIT improved post-ischemic LV functional recovery and reduced infarct size. This increase in ischemic-tolerance was accompanied by an improved mitochondrial function as well as reduced MVO2. The present study highlights the therapeutic potential of exercise training with regard to improving the ischemic-tolerance in hearts following obesity and insulin resistance. This study also emphasizes the beneficial effect of exercise on cardiac energetics and mitochondrial function in obesity/diabetes.